2003
DOI: 10.1046/j.1471-6712.2003.00230.x
|View full text |Cite
|
Sign up to set email alerts
|

Family carers of ICU survivors: A survey of the burden they experience

Abstract: Intensive care unit (ICU) survivors may experience deterioration in their quality of life for months following their return home, with families assuming a caregiving role. The aim of this study was to measure the burden associated with caring for a family member who had been critically ill. The study also sought to describe the relationship between three factors (filial obligation, social support, self-efficacy) and caregiver burden. Seventy-one family carers, 51 females (72%) and 20 (28%) males of long-term i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 60 publications
0
40
0
4
Order By: Relevance
“…79 Existing evidence suggests that providing this care may have a deleterious impact on caregivers, and may compromise HRQOL compared with age-and sex-matched persons. 80 Furthermore, significant mental health issues have been reported among caregivers, including PTSD, 81 emotional distress, 80,82-84 caregiver burden, 85 depression, 86 and anxiety. 87 In a recent review, Johnson and colleagues 88 concluded that caregivers experience burden from the patient's physical and psychological dysfunction and the challenges of managing complex care in the home.…”
Section: Caregiver and Family Burden In Critical Illnessmentioning
confidence: 99%
“…79 Existing evidence suggests that providing this care may have a deleterious impact on caregivers, and may compromise HRQOL compared with age-and sex-matched persons. 80 Furthermore, significant mental health issues have been reported among caregivers, including PTSD, 81 emotional distress, 80,82-84 caregiver burden, 85 depression, 86 and anxiety. 87 In a recent review, Johnson and colleagues 88 concluded that caregivers experience burden from the patient's physical and psychological dysfunction and the challenges of managing complex care in the home.…”
Section: Caregiver and Family Burden In Critical Illnessmentioning
confidence: 99%
“…Numerous researchers have conducted studies of the experiences of critically ill patients and the needs of their family members (Beach et al, 1992;Burr, 1996;Davies, 2000;Fridlund et al, 1993;Chien et al, 2006;Chui and Chan, 2007;Foster and Chaboyer, 2003;* Geary et al, 1994* Geary et al, , 1997Gortner et al, 1988;Holl, 1993;Johnson et al, 2001;Mishel and Murdaugh, 1987;Mutran et al, 1997;Parker, 1997;Saxe-Braithwaite and Chapman, 1992;Simpson, 1991). However, few have investigated the experiences and interactions that make up the informal support and care of both these groups of patients and their main family carers (MFC) simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…Close to 60% of ICU survivors who received long-term mechanical ventilation still required the assistance of a family caregiver 1 year after their critical illness. 22 Caregivers may experience compromised HRQOL 21 and mental health, including posttraumatic stress disorder, 31 emotional distress, 21,32-34 caregiver burden, 35 depression, 36 and anxiety. 37 As we continue to complete our understanding of the full spectrum of disability in our patients, there is also some urgency to characterize the parallel experience in the caregiver during and after the episode of critical illness and how the outcomes and challenges in each group are interrelated.…”
Section: Caregiver As a Modifier Of The Spectrum Of Disabilitymentioning
confidence: 99%